Trace detection of homologues and isomers based on hollow mesoporous silica sphere photonic crystals. Issue 5 (7th August 2017) - Xiong, Chengjia; Zhao, Jiupeng; Wang, Lebin; Geng, Hongbin; Xu, Hongbo; Li, Yao
Abstract : Hollow mesoporous silica sphere photonic crystal sensors show high sensitivity and distinguishability in detecting homologues and isomers. Abstract : A photonic crystal (PC) sensor that can detect homologues and isomers with very similar refractive indices through stopband shifts has been prepared from highly monodispersed hollow mesoporous silica spheres (HMSSs) for the first time. The HMSS PC shows two obvious reflection peaks, the positions of which are related to the inner and outer diameters of the HMSSs. When the HMSS PC sensors are infiltrated with 10 μL of homologues or isomers, the positions of the second reflection peaks remain nearly unchanged, while the first reflection peaks shift between 60 and 200 nm. The difference in the refractive indices of n -propanol and iso-propanol is only 0.008; however, the difference in the stopband shifts is approximately 25 nm, showing high sensitivity in distinguishing homologues and isomers of the HMSS PC. The proposed strategy provides a convenient, cheap trace detection method to distinguish homologues and isomers.